Propriedades nutricionais e funcionais de palma (Opuntia ficus-indica) e sua utilização no processamento de geleias - Santos, Marília Cícera Gomes dos (2014)
Natural from Mexico, the family of cactus corresponds to approximately 130 genera and 1500 species, lying mainly distributed in arid and semi-arid regions of the New World. One way to include this vegetable in human nutrition is process it into jelly. The objective of this research was to develop jelly palm (Opuntia ficus-indica) that meets the parameters physical, chemical, microbiological and sensory of quality, and characterize it in terms of nutritional composition and antioxidant potential. Formulations for the jelly palm were developed using 23 factorial design with 3 central points totaling 11 trials; having as independent variables the concentrations of sucrose in relation to pulp concentration (S/P), citric acid concentration (A) and concentration of pectin (P). The dependent variables were: pH, water activity, instrumental color (brightness, chromaticity a * and b *), texture, soluble solids and titratable acidity. Considering the parameters of physical quality and chemical, formulations of jelly palm were selected and conducted for microbiological analysis, which allowed the realization of sensory analysis without causing health risk assessors. The sensory characteristics were obtained by means of acceptance test and purchase s intent test. The formulation that received the best acceptance rates and lower sugar content was sent to continue the study in order to evaluate their nutritional and functional properties. The results of the experimental design demonstrated that pH, texture, soluble solids and titratable acidity were the dependent variables with the biggest influence on the quality of jelly palm due to models showed significance with 95 % confidence. The formulation with 35 % sucrose, 65 % pulp, 0.55 % citric acid and 0.5 % pectin was selected to continue the study due to lower sugar content and higher amount of pulp. The nutritional composition showed that the jelly palm is a compatible product to marmalades, has significant quantities of bioactive compounds and is low calorie. However it has an expressive little capacity to sequester the DPPH and ABTS radical. These data make the palm a product with technological feasibility.